Anisotropic energy transfer in crystalline chromophore assemblies. Issue 1 (December 2018) - Haldar, Ritesh; Jakoby, Marius; Mazel, Antoine; Zhang, Qiang; Welle, Alexander; Mohamed, Tawheed; Krolla, Peter; Wenzel, Wolfgang; Diring, Stéphane; Odobel, Fabrice; Richards, Bryce; Howard, Ian; et al.
Abstract An ideal material for photon harvesting must allow control of the exciton diffusion length and directionality. This is necessary in order to guide excitons to a reaction center, where their energy can drive a desired process. To reach this goal both of the following are required; short- and long-range structural order in the material and a detailed understanding of the excitonic transport. Here we present a strategy to realize crystalline chromophore assemblies with bespoke architecture. We demonstrate this approach by assembling anthracene dibenzoic acid chromophore into a highly anisotropic, crystalline structure using a layer-by-layer process. We observe two different types of photoexcited states; one monomer-related, the other excimer-related. By incorporating energy-accepting chromophores in this crystalline assembly at different positions, we demonstrate the highly anisotropic motion of the excimer-related state along the [010] direction of the chromophore assembly. In contrast, this anisotropic effect is inefficient for the monomer-related excited state. Exciton diffusion length and directionality are important parameters in artificial photosynthetic devices. Here, the authors present a way to make crystalline chromophore assemblies with bespoke architecture, fabricating one exhibiting anisotropic exciton transport properties.